The mysticism of life versus the mysticism of death. Comparison of the Saint Teresa of Jesus with the philosophical view of Giorgio Agamben - Moreno-Szypowska, Jadwiga Clea (Filozofia Chrześcijańska, 2019)
Reading the text of the main representative of Spanish mysticism, which is Saint Teresa of Jesus, we can see similarities with the philosophical refl ections of the modern thinker Giorgio Agamben. In both of them we fi nd an analogous approach to the issues that concern them the most: for the mystic it is God, for Agamben, language. Poetic images used by Saint Teresa of Jesus, are transforming into the philosophical concepts used by Agamben. The thinking of both is similar, although the message is completely diff erent. Filled with the “faith, hope and love” of Saint Teresa of Jesus wants to draw a path, a leading soul to God, a synonym for life, and Agamben, infl uenced by the thoughts of Hegel and Heidegger, outlines a situation in which a lost human being is in a cul-de-sac ending with terrifying death wall. Hence the mysticism of the sixteenth century can be called the mysticism of life, while philosophical considerations over the language of the twentieth century, the mysticism of death.